Examining the effectiveness of dissuasive taxes as a policy tool for reducing tobacco and alcohol consumption in Cameroon: A welfare and microsimulation analysis - Paul Tadzong Mouafo; Hilaire Nkengfack; Rodrigue Nobosse Tchoffo; Nelson Derrick Nguepi; Edmond Noubissi Domguia (Heliyon)
Deterrent taxes are a crucial policy tool for reducing the consumption of harmful products like tobacco and alcohol. However, assessing dissuasive taxes impact different income groups is important to ensure that their burden is not disproportionately borne by low-income households. This study examines the effectiveness of deterrent taxes as an economic policy tool for reducing tobacco and alcohol consumption in Cameroon. We analyse the impact on household welfare and distributional effects using microsimulation analysis. The data come from the Cameroon Household Living Conditions Survey and the 2022 tax records. Our methodology is based on a dynamic computable general equilibrium (CGE) model enriched with an addiction model. The results indicate that deterrent taxes can significantly reduce the consumption of these harmful products but also have regressive effects on low-income households. In response, we recommend the adoption of a progressive tax structure and the establishment of targeted support programmes to mitigate the negative impact on vulnerable populations.